2023
DOI: 10.1002/chem.202300034
|View full text |Cite
|
Sign up to set email alerts
|

White Light‐Emitting Electrochemical Cells Employing Phosphor‐Sensitized Thermally Activated Delayed Fluorescence to Approach All‐Phosphorescent Device Efficiencies

Abstract: Solid-state light-emitting electrochemical cells (LECs) show promising advantages of simple device architecture, low operation voltage, and insensitivity to the electrode work functions such that they have high potential in low-cost display and lighting applications. In this work, novel white LECs based on phosphor-sensitized thermally activated delayed fluorescence (TADF) are proposed. The emissive layer of these white LECs is composed of a blue-green phosphorescent host doped with a deep-red TADF guest. Effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…By carefully selecting appropriate ligands, it becomes possible to achieve high luminance efficiency and create multicolor LECs. ,,, To obtain emission at 450–650 nm, one approach consists of using either electron-withdrawing group-substituted ligands (such as F) or electron donating group-substituted ligands (such as CH 3 or OCH 3 ) showing a high-lying lowest-unoccupied molecular orbital (LUMO) while azole-containing moieties as the highest-occupied molecular orbital (HOMO). It was recently shown that the replacement of the pyridine ring of C∧N ligand by the five-membered nitrogen-rich heterocyclic moiety, e.g., pyrazole, triazole, or tetrazole, gives in most cases a hypsochromically shifted PL emission due to the HOMO stabilization . According our previous work, tethering electron-withdrawing fluorine atoms onto phenylpyrazole and introducing electron-donating CH 3 moieties onto bipyridine (bpy) lead to an enhanced band gap ( E g ) and excellent performance of a maximal external quantum efficiency (EQE max ) = 4.6% in blue-green LECs. , In 2020, Lu et al successfully developed a yellow complex known as YIr, denoted as [Ir­(bppz) 2 (Bphen)]­PF 6 , using the host–guest strategy and embedding a diffusive layer, achieving a promising EQE max up to 23.7% at 565 nm, marking it as the best performance observed to date for yellow LECs . In the subsequent year, a green complex, [Ir­(CF 3 -dPhTAZ) 2 (bpy)]­PF 6 , which introduced by He et al achieved an EQ E max of 10.4% at 525 nm while effectively mitigating phosphorescence concentration-quenching using the C∧N ligand …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By carefully selecting appropriate ligands, it becomes possible to achieve high luminance efficiency and create multicolor LECs. ,,, To obtain emission at 450–650 nm, one approach consists of using either electron-withdrawing group-substituted ligands (such as F) or electron donating group-substituted ligands (such as CH 3 or OCH 3 ) showing a high-lying lowest-unoccupied molecular orbital (LUMO) while azole-containing moieties as the highest-occupied molecular orbital (HOMO). It was recently shown that the replacement of the pyridine ring of C∧N ligand by the five-membered nitrogen-rich heterocyclic moiety, e.g., pyrazole, triazole, or tetrazole, gives in most cases a hypsochromically shifted PL emission due to the HOMO stabilization . According our previous work, tethering electron-withdrawing fluorine atoms onto phenylpyrazole and introducing electron-donating CH 3 moieties onto bipyridine (bpy) lead to an enhanced band gap ( E g ) and excellent performance of a maximal external quantum efficiency (EQE max ) = 4.6% in blue-green LECs. , In 2020, Lu et al successfully developed a yellow complex known as YIr, denoted as [Ir­(bppz) 2 (Bphen)]­PF 6 , using the host–guest strategy and embedding a diffusive layer, achieving a promising EQE max up to 23.7% at 565 nm, marking it as the best performance observed to date for yellow LECs . In the subsequent year, a green complex, [Ir­(CF 3 -dPhTAZ) 2 (bpy)]­PF 6 , which introduced by He et al achieved an EQ E max of 10.4% at 525 nm while effectively mitigating phosphorescence concentration-quenching using the C∧N ligand …”
Section: Introductionmentioning
confidence: 99%
“… 33 According our previous work, tethering electron-withdrawing fluorine atoms onto phenylpyrazole and introducing electron-donating CH 3 moieties onto bipyridine (bpy) lead to an enhanced band gap ( E g ) and excellent performance of a maximal external quantum efficiency (EQE max ) = 4.6% in blue-green LECs. 30 , 34 36 In 2020, Lu et al successfully developed a yellow complex known as YIr, denoted as [Ir(bppz) 2 (Bphen)]PF 6 , using the host–guest strategy and embedding a diffusive layer, achieving a promising EQE max up to 23.7% at 565 nm, marking it as the best performance observed to date for yellow LECs. 20 In the subsequent year, a green complex, [Ir(CF 3 -dPhTAZ) 2 (bpy)]PF 6 , which introduced by He et al achieved an EQ E max of 10.4% at 525 nm while effectively mitigating phosphorescence concentration-quenching using the C∧N ligand.…”
Section: Introductionmentioning
confidence: 99%